The buffalo supply chain in northeast of Brazil - Ricardo Alexandre Silva Pessoa; Luis Henrique Romani de Campos (Revista Científica)
Studies and analyses of supply chains make it possible to assess the different approaches such as technologies ,public and private policies, business strategies, and new arrangements and to identify the issues such as improved performance and competitiveness. The objective of this work was to analyze the buffalo (Bubalus bubalis) production chain and the contribution of Porter’s Five competitive forces to the buffalo production chain in Northeast Brazil. For that, research was carried out through information obtained in the literature. Interviews and questionnaires were applied to the companies involved in the activity. It was observed that the main limiting factor on the buffalo chain in Northeast Brazil is the need for more information about the species, which makes it difficult for a more accurate analysis. Concerning daily activity, the production chain is well organized. Five small and medium-sized dairies process buffalo milk in the region. Other small-scale enterprises are also found. Regarding buffalo breeding for meat, the numbers associated with the activity in Northeast Brazil need to be clarified since buffalo meat is sold as beef, confusing the buffalo herd with the bovine herd. The commercialization of the buffalo carcass as bovine is the main factor responsible for this condition. Buffalo meat needs to be marketed as buffalo meat for the activity to be recognized. The use of Porter’s Five Forces efficiently describes the interconnected processes associated with the buffalo production chain in Northeast Brazil and contributes to improving the chain.